Aggregation-induced emission leading to two distinct emissive species in the solid-state structure of high-dipole organic chromophores. Issue 32 (9th August 2021) - Witte, Felix; Rietsch, Philipp; Nirmalananthan-Budau, Nithiya; Weigert, Florian; Götze, Jan P.; Resch-Genger, Ute; Eigler, Siegfried; Paulus, Beate
Abstract : Fluorescence lifetime measurements reveal two emissive species in the solid-state structure of high-dipole chromophores unravelled by high-level quantum-chemical approaches to originate from both monomers and H-type dimers. Abstract : The concept of aggregation-induced emission represents a means to rationalise photoluminescence of usually nonfluorescent excimers in solid-state materials. In this publication, we study the photophysical properties of selected diaminodicyanoquinone (DADQ) derivatives in the solid state using a combined approach of experiment and theory. DADQs are a class of high-dipole organic chromophores promising for applications in non-linear optics and light-harvesting devices. Among the compounds investigated, we find both aggregation-induced emission and aggregation-caused quenching effects rationalised by calculated energy transfer rates. Analysis of fluorescence spectra and lifetime measurements provide the interesting result that (at least) two emissive species seem to contribute to the photophysical properties of DADQs. The main emission peak is notably broadened in the long-wavelength limit and exhibits a blue-shifted shoulder. We employ high-level quantum-chemical methods to validate a molecular approach to a solid-state problem and show that the complex emission features of DADQs can be attributed to a combination of H-type aggregates, monomers, and crystal structure defects.